A One-Dimensional Hemodynamic Model of the Coronary Arterial Tree - Duanmu, Zheng; Chen, Weiwei; Gao, Hao; Yang, Xilan; Luo, Xiaoyu; Hill, Nicholas A. (Frontiers in Physiology, 2019)
One dimensional (1D) hemodynamic models of arteries have increasingly been applied to the coronary circulation. In this study, we have adopted flow and pressure profiles in Olufsen's 1D structured tree as coronary boundary condition, with terminals coupled to the dynamic pressure feedback resulted from the intra-myocardial stress because of ventricular contraction. We model a trifurcation structure of the examplar coronary tree as two adjacent bifurcations. The estimated results of blood pressure and flow rate from our simulation agree well with the clinical measurements and published data. Furthermore, the 1D model enables us to use wave intensity analysis to simulate blood flow in the developed coronary model. Six characteristic waves are observed in both left and right coronary flows, though the waves' magnitudes differ from each other. We study the effects of arterial wall stiffness that on coronary blood flow in the left circumflex artery (LCX). Different diseased cases indicate distinct pathological reactions of the cardiovascular system can be better distinguished though WI analysis, which show agreement with the clinical observation. Finally, the feedback pressure in terminal vessels and measurement deviation are also investigated by changing parameters in LCX. We find that larger feedback pressure increases the backward wave and decreases the forward one. Although simplified, this 1D model provides new insight into coronary hemodynamics in healthy and diseased conditions. We believe that this approach offers reference resources for studies on coronary circulation diseases diagnosis, treatment and simulation.